Aerial mapping using high resolution digital camera and unmanned aerial vehicle for geographical information system - Ahmad, Anuar (2010)
In aerial photogrammetry, aerial photographs are acquired using aerial camera and light aircraft as a platform. The aerial photographs are usually processed for mapping such as for production of topographic map and other special purpose map known as thematic map. However, this method is expensive and suitable for large area but it is not practical for mapping small area. This study concentrates on the use of high resolution digital camera and a very light platform known as unmanned aerial vehicle (UAV) as data acquisition system in capturing digital aerial photographs. The acquired digital aerial photographs were processed using image processing software to produce digital map and digital orthophoto. The results showed that an accuracy of sub-meter can be obtained using the employed method. In Geographical Information System (GIS), it is quite common that topographic map and orthophoto are used as a base map. Hence, the findings from this study could also be used as an input for GIS. Not to forget, the photogrammetric technique could be used not only for mapping but it could also be used for any environmental protection and conservation.